Effect of Fatty Acyl Structure on the Foam Properties of N-Acyl Serinate Surfactants - Li, You; Wang, Na; Zhang, Yuanyuan; Zhao, Li; Ran, Zhaoming; Wang, Ce; Mekkaoui, Aicha; Xu, Baocai (Journal of Oleo Science, 2023)
Amino acid surfactants derived from animal/vegetable oils and amino acids have attracted growing interest in surfactant industry. The relationship between the molecular structures of natural building blocks and the performance of the derived surfactants has become a significant subject in their application. A series of serinate surfactants with different characteristic acyls were synthesized. The specific effect of the fatty acyl structures, namely, the hydrocarbon chain length, the number of C=C bonds, and hydroxyl substituent, on the foam properties and interfacial behaviors were revealed. The serinate surfactants with long fatty acyls showed better interfacial activity and were more closely arranged at the interface, thus improving the foam stability. But the long fatty acyls also decreased the water solubility, and lead to the decreased the foamability of N-stearyl serinate surfactant. The C=C bonds in the fatty acyl improved the water solubility of the surfactants. But multiple cis C=C bonds caused the bend of hydrocarbon chains, which was unfavorable for the close arrangement of surfactant molecules, thus leading to the decrease of the foam stability. The hydroxyl group in the ricinoleoyl decreased the intermolecular van der Waals interactions and hindered the close arrangement of ricinoleoyl serinate surfactant molecules, leading to the decrease of the foam stability.